Current practice of assessing students’ sustainability competencies: a review of tools - Redman, Aaron; Wiek, Arnim; Barth, Matthias (Sustainability science, 2021)
While there is growing agreement on the competencies sustainability professionals should possess as well as the pedagogies to develop them, the practice of assessing students’ sustainability competencies is still in its infancy. Despite growing interest among researchers, there has not yet been a systematic review of how students’ sustainability competencies are currently assessed. This review article responds to this need by examining what tools are currently used for assessing students’ sustainability competencies to inform future practice. A systematic literature review was conducted for publications through the end of 2019, resulting in 75 relevant studies that detail the use of an assessment tool. We analyzed the described tools regarding their main features, strengths and weaknesses, as well as potential improvements. Based on this analysis, we first propose a typology of eight assessment tools, which fall into three meta-types: self-perceiving, observation, and test-based approaches, providing specific examples of practice for all tools. We then articulate strengths and weaknesses as well as potential improvements for each tool (type). This study structures the field of sustainability competency assessment, provides a criteria-based overview of the currently used tools, and highlights promising future developments. For the practice, it provides guidance to sustainability (science) instructors, researchers, and program directors who are interested in using competencies assessment tools in more informed ways.